Assessment of Food Intake, Obesity, and Health Risk among the Homeless in Rhode Island. Issue 5 (16th February 2015) - Martins, Diane C.; Gorman, Kathleen S.; Miller, Robin J.; Murphy, Leah; Sor, Sekboppa; Martins, Jonah C.; Vecchiarelli, Maria L.
Abstract Objective The objective of this study was to examine the relationship between the nutritional status, incidence of food insecurity, and health risk among the homeless population in Rhode Island. Design and Sample This correlational study utilized a convenience sample of 319 homeless adults from Rhode Island's largest service agency for the homeless. Information on use of services such as access to emergency foods, shelters, and the Supplemental Nutrition Assistance Program (SNAP) was requested. Measures Food security was measured by the six‐item subset of the USDA Food Security Core Module. Anthropometric measures included height, weight, and waist circumference. A 24‐hr dietary recall was collected to determine the food intake for a subset of participants who agreed to supply this information (n = 197). Conclusion Average dietary recall data indicated insufficient intake of vegetables, fruit, dairy, and meats/beans. It also indicated excessive intake of fats. Of the 313 participants, 29.4% were overweight and 39% were obese. Over 94% of the participants were food insecure, with 64% of this subset experiencing hunger. Fifty‐five percent of the participants were currently receiving SNAP benefits. The majority of the sample was found to be food insecure with hunger.